Simultaneous Decolorization of Tartrazine and Production of H2 in a Combined Electrocoagulation and Photocatalytic Processes using CuO-TiO2 Nanotube Arrays: Literature Review and Experiment - S. Slamet; Laily Fitri Pelawi; Muhammad Ibadurrohman; Rike Yudianti; R. Ratnawati (Universitas Pendidikan Indonesia, 2022)
We reported the simultaneous decolorization of tartrazine and H2 production via electrocoagulation and photocatalysis using CuO-doped TiO2 nanotube arrays (TNTA) composites. Tartrazine was removed by the combination of adsorption, electrocoagulation, and photocatalytic degradation, while H2 was produced through water reduction at the cathode and water splitting process on the photocatalyst surface. The photoreactor contains CuO-TNTA as a photocatalyst and is equipped with an 80-W UV lamp. Deposition of CuO on TNTA was conducted using a successive ionic layer adsorption and reaction (SILAR) method. The nanotubular of the TNTA as well as the distribution of CuO were evaluated employing FESEM and HRTEM. XRD patterns confirmed weak diffraction of CuO and TNTA revealing an anatase crystallite phase. The band gap of the CuO-TNTA was also found to be redshifted from that of pure TNTA. The simultaneous processes with the combined systems (20 V, pH = 11) managed to remove 80% of tartrazine while producing a high H2 yield (1.84 mmol), significantly higher than those obtained by each process.